Predictors of Response to Cognitive-Behavioral Therapy for Body Dysmorphic Disorder. Issue 4 (July 2019) - Greenberg, Jennifer L.; Phillips, Katharine A.; Steketee, Gail; Hoeppner, Susanne S.; Wilhelm, Sabine
Abstract: Body dysmorphic disorder (BDD) is a common and distressing or impairing preoccupation with a perceived defect in physical appearance. Individuals with BDD engage in time-consuming rituals to check, hide, or "fix" their appearance or alleviate distress. BDD is associated with substantial psychosocial impairment and high rates of depression, hospitalization, and suicidality. Cognitive-behavioral therapy (CBT) is the treatment of choice for BDD, but not everyone benefits. We examined predictors of CBT-related improvement, an important topic that has received very limited investigation. Treatment was delivered in weekly individual sessions over 18–22 weeks. Results indicated that greater motivation/readiness to change (University of Rhode Island Change Assessment Questionnaire), greater treatment expectancy (Treatment Credibility/Expectancy Questionnaire), and better baseline BDD-related insight (Brown Assessment of Beliefs Scale) significantly predicted better CBT response at posttreatment. Baseline BDD symptom severity and depression did not predict outcome, suggesting that even patients with more severe BDD and depressive symptoms can benefit from CBT for BDD. Efforts should be aimed at enhancing readiness to change and confidence in the treatment at treatment onset as well as addressing the poor insight that often characterizes BDD. Highlights: Examined predictors of response to cognitive-behavioral therapy for BDD Readiness to change, treatment expectancy, and BDD-related insight predicted outcome BDD symptom severity and depression did not predict outcome